2019
DOI: 10.1002/oby.22540
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention Interventions and Implications for Energy Balance in the United States and Mexico: A Systematic Review of the Evidence and Meta‐Analysis

Abstract: Objective Obesity is preventable and yet continues to be a major risk factor for chronic disease. Multiple prevention approaches have been proposed across multiple settings where people live, work, learn, worship, and play. This review searched the vast literature on obesity prevention interventions to assess their effects on daily energy consumed and energy expended. Methods This systematic review (PROSPERO registration CRD42017077083) searched seven databases for syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…A review of the forest plots from a meta-analysis of school-based child obesity prevention interventions revealed that the vast majority of effects hovered near zero [ 11 ]. When reviewing the impact of all child obesity prevention trials on energy balance [ 12 ], only small, weak effects on energy consumed and energy expended were noted. Even longer term (one year or longer) trials did not impact BMI [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the forest plots from a meta-analysis of school-based child obesity prevention interventions revealed that the vast majority of effects hovered near zero [ 11 ]. When reviewing the impact of all child obesity prevention trials on energy balance [ 12 ], only small, weak effects on energy consumed and energy expended were noted. Even longer term (one year or longer) trials did not impact BMI [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This holds even though we used an intervention estimate that had the strongest effect on reducing energy intake in meta-analyses (11). This is not sufficient to reverse obesity trends.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we assume that health education campaigns reduce individuals’ daily energy intake by 73 kcal. This estimate was derived as the mean difference in daily caloric intake between treated and control groups in 10 RCTs (11) weighted by the size of the study population. We convert this to a change in body weight using a model (26) that accounts for biological dynamics when individuals lose weight, such as the eventual plateau after initial weight loss.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature reviewed, some research studies on different populations address EB, particularly to understand the global trend toward obesity [13][14][15][16]. Additionally, the term 'energy imbalance gap' has been introduced to better understand for public health policies, 3 of 17 in which the difference between energy intake and expenditure can used a reference to establish whether weight can reach equilibrium and prevent weight gain [17,18].…”
Section: Introductionmentioning
confidence: 99%